The Impact of Accounting Information Systems’ Characteristics on Organizational Performance by Using Leadership Style: A Field Study on Saudi Industrial Corporate - Alaseeri, Shahad Ahmed; Obaid, Rawia Reda (Journal of Economic, Administrative and Legal Sciences, 2024)
The current study aimed to investigate the impact of characteristics of accounting information systems on organizational performance using leadership styles in Saudi industrial companies. The study’s problem focused on understanding how the characteristics of accounting information systems affect organizational performance (planning, control) using leadership styles in Saudi industrial companies. The importance of accounting information systems lies in their direct utility across various levels of employees in companies, particularly in areas of control, auditing, and decision-making. The study adopted a descriptive-analytical approach and utilized a survey as a tool to measure study variables, administered to managers working in accounting, accountants, and internal auditors in Saudi industrial companies. The study concluded the following: Saudi industrial companies apply accounting information systems to a high degree, and they also employ leadership styles effectively. The study recommended the continuous application of accounting information system characteristics by Saudi industrial companies and emphasized the need to develop methods for their implementation. It also recommended raising awareness among employees in Saudi industrial companies regarding the characteristics of accounting information systems through workshops, courses, and scientific conferences dedicated to this topic, and encouraging these parties to adhere to International Financial Reporting Standards through various available means.